Pertanggungjawaban Pidana Terhadap Pelaku Tindak Pidana Pembunuhan Karena Membela Diri Yang Melampaui Batas (Noodweer Excess) - Dwi Putri Nofrela; Erdianto '; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Self-defense is a form of human nature in protecting themselves from the various threats that could threaten the life safety, morals, and property belonging to themselves. But sometimes the defense is done in case of emergency could have provide disadvantage to other people so that their excessively limits on defenses (noodweer excess). The regulation of self-defense in urgent situations regulated in Pasal 49 the KUHP. In the article it is said that a person who has committed to the defense of life, morals or property belongin to either for themselves or another person can not be convicted.Decision of Pengadilan Tinggi Palembang No. 170 / Pid / 2011 / PT.PLG, Decision of Pengadilan Negeri Lubuk Linggau No. 794 / Pid.B / 2014 / PN LLG and Decision of Pengadilan Negeri Semarang No. : 1002 / Pid.B / 2008 / PN. SMG, has implemented Pasal 49 KUHP within the judge's ruling, which the judge gave the accused acquitted because the judge found the element of justification of the actions undertaken so that the perpetrators can not be held accountable.But in contrast to Decision of Pengadilan Tinggi Pekanbaru No. 09 / Pid.B / 2013 / PTR because the judge did not apply Pasal 49 paragraph (2) KUHP. Ratna (the murder in self-defense) was sentenced to imprisonment for 2 years and 6 months. In fact, if observed the Ratna act in relation to Article 49 paragraph (2) Criminal Code can not meet all the elements in the aforementioned article for protecting the Ratna sought to honor him for acts committed Adi Charlie (the murder victim in self-defense).Key Words : Criminal Liability - Noodweer Excess – Criminal Act